2017
DOI: 10.7602/jmis.2017.20.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy after Upper Abdominal Surgery : Is It Feasible Even after Gastrectomy?

Abstract: Purpose: Laparoscopic cholecystectomy (LC) is now a standard operation for benign gallbladder (GB) disease. However, previous upper abdominal surgery (UAS) has been regarded as a relative contraindication for LC. The purpose of this study was to examine the effects of history of upper abdominal surgery including gastrectomy on the operative and postoperative results of LC. Methods:A total of 769 patients underwent LC between March 2008 and December 2015, and the surgical outcomes of 45 patients who had a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The severity of adhesion, on the other hand, has a greater impact than the sort of past operation that can be addressed with a proper laparoscopic approach. 19 As for safety and conversion rate, safety should and must be always the corner stone for evaluating and judging any new emerging technique and it should be never compromised for the wrong goals. The request and concern in ''scarless'' surgery cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of adhesion, on the other hand, has a greater impact than the sort of past operation that can be addressed with a proper laparoscopic approach. 19 As for safety and conversion rate, safety should and must be always the corner stone for evaluating and judging any new emerging technique and it should be never compromised for the wrong goals. The request and concern in ''scarless'' surgery cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in operative time were prominent in different studies. For example Karayiannakis et al [5] reported a mean time of 66.4±34.2 minutes, while in Akyurek et al [15] study, it was 57± 9.8 minutes, Lee et al [26] reported 144.2± 56.1 minutes, Kohli et al [14] reported 76.2±13.2 minutes, and Fanaei et al reported a mean time of 75.0±3.2 minutes. The prolonged operative time noted in the study of Lee et al [26] was a consequence of being applied among patients who had a scar of previous gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy performed at the time of primary surgery may be beneficial considering that subsequent cholecystectomy is more challenging after upper abdominal surgery and has an increased risk for bile duct injuries and a longer operation time [ 7 , 8 ]. Further, concomitant cholecystectomy might reduce the risk of disease recurrence around the gallbladder.…”
Section: Introductionmentioning
confidence: 99%